Anafilaxia ao látex. - M B Ferreira; E Pedro; M A Barbosa; A G Carlos (Acta Médica Portuguesa, 1997)
The authors present two case-reports of Latex Anaphylaxis--a rare but dangerous manifestation of latex allergy--, one in a patient belonging to a risk group and the other in a patient without previously identified risk factors. A review of latex allergy, and particularly of latex anaphylaxis, is made focusing on risk groups, aetiology, diagnosis, prevention and therapy. This paper also intends to draw attention to this health problem and stress the fact that it raises several medical and non-medical issues, requiring a multidisciplinary approach and discussion.